A characterization of height-based extensions of principal filtral opportunity rankings (2013)
A parameterized characterization of height-based total extensions of principal filtral opportunity rankings is provided and shown to include, as a special case, a version of the well-known Pattanaik-Xu characterization of the cardinality-based ranking.